An adoption framework for mobile augmented reality games: The case of Pokémon Go. (November 2017) - Rauschnabel, Philipp A.; Rossmann, Alexander; tom Dieck, M. Claudia
Abstract: Pokémon Go was the first mobile augmented reality (AR) game to reach the top of the download charts of mobile applications. However, little is known about this new generation of mobile online AR games. Existing theories provide limited applicability for user understanding. Against this background, this research provides a comprehensive framework based on uses and gratification theory, technology risk research, and flow theory. The proposed framework aims to explain the drivers of attitudinal and intentional reactions, such as continuance in gaming or willingness to invest money in in-app purchases. A survey among 642 Pokémon Go players provides insights into the psychological drivers of mobile AR games. The results show that hedonic, emotional, and social benefits and social norms drive consumer reactions while physical risks (but not data privacy risks) hinder consumer reactions. However, the importance of these drivers differs depending on the form of user behavior. Highlights: The study develops a framework for augmented reality games. The framework incorporates findings from numerous disciplines. The authors identify novel benefits and risks factors. The study also investigates drivers of invest in-app purchases.